STUDENTS' HABIT IN SINGING ENGLISH POP SONGS AND THEIR VOCABULARY MASTERY: A CORRELATIONAL STUDY - Maulana Wildan Naufal (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
One of the strategies that can be used to increasing vocabulary is singing English pop song. This study aims to determine whether there is a correlation between students’ habit in singing English pop songs and their vocabulary mastery. In this field, the researcher used the quantitative method with correlation design. The researcher did the research with Students Choir of UKM Paduan Suara Mahasiswa Bunga Almamater Universitas Islam Malang batch 23 as subject of the research. The researcher collected the data used questionnaire and vocabulary test. Both of them are online tested using Google form. Then, the researcher analyze the data using SPSS 20.0. The findings of the research, The obtained R-value of 0.730 indicated a high correlation at the 0.60 - 0.80 level. The R-table for df 37 was 0.325 at 0.05 level of significance. Further, because the R-obtained was higher than the R-table (0,730> 0,325), the coefficient correlation obtained was significant and the hypothesis in this research was accepted. English students mastering the vocabulary including function and content words, while non English student mastering the vocabulary mostly only the content words. This study expected to students can realize the importance of strategy in learning a new language. As English lecturers, they must be gaining the strategies that make students enjoy in the English class, especially vocabulary mastery. Therefore, it is recommended for the future researcher to conduct the same research on a different subject and also can investigate the correlation between singing English pop songs and the other skills.